2014
DOI: 10.5539/emr.v3n2p52
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement by Logistics Collaboration Management Model for Orchid Flower Industry in Thailand

Abstract: This paper aims to present the logistics collaboration management model and performance improvement of orchid flower firms in logistics activities for growers and exporters. The collaboration results improving cost, time and reliability to all parties in the chain. The collaboration management model becomes firms' management tools for competitive advantage among rivals in the industry. The logistics performance indicator model uses to measure the activities between pre and post collaboration. The research cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The OC transition typically involves one or more LSPs that manage and perform logistics activities on behalf of retailers. Such logistics activities include warehousing, transportation, demand forecasting and planning, order processing, inventory management, material handling and packaging, customer service and reverse logistics (Hotrawaisaya et al, 2014). Retailers and LSPs need to work together to develop logistics systems that can handle multiple flows and returns.…”
Section: Shipper-provider Relationships In Omni-channel Retailingmentioning
confidence: 99%
“…The OC transition typically involves one or more LSPs that manage and perform logistics activities on behalf of retailers. Such logistics activities include warehousing, transportation, demand forecasting and planning, order processing, inventory management, material handling and packaging, customer service and reverse logistics (Hotrawaisaya et al, 2014). Retailers and LSPs need to work together to develop logistics systems that can handle multiple flows and returns.…”
Section: Shipper-provider Relationships In Omni-channel Retailingmentioning
confidence: 99%
“…Another opinion by (Hotrawaisaya, C., Chandraprakaikul, W., & Suthikarnarunai, N, 2014) showed that Logistics performance indicators (LPI) had criteria that include costs, time, and reliability, which can measure the logistics operations performance among partners in the supply chain. Furthermore, Stank et al (2003) revealedthat relational performance provides service to suppliers with more detailed information about both customers' needs which help the service providers to focus on operational plans.…”
Section: The Relationship Between Organizational Logistics Performance and Customer Satisfactionmentioning
confidence: 99%
“…In logistics collaboration, logistics activities involve joint planning and information sharing, with less focus on strategic planning (Sandberg, 2007). These logistics activities include customer service, demand forecasting and planning, transportation, order processing, warehousing, inventory management, material handling and packaging, reverse logistics, and logistics communication (Hotrawaisaya et al , 2014). However, we conduct a broad overview of logistics collaboration that covers many aspects of supply chain collaboration (Sandberg, 2007).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Logistics performance indicators and criteria include costs, time, and reliability (Hotrawaisaya et al , 2014), which can be used to measure the logistics operations performance among partners in the supply chain. Several specific criteria are particularly important, including on-time delivery, lead time, error-free delivery, scheduled delivery fulfillment, order fill rate, damaged orders, delivery of urgent orders, deliveries in periods of high demand, short transit time, availability of cargo space, and the condition of vehicles and containers (Lai et al , 2002; Lu, 2003; Simatupang and Sridharan, 2002; Vieira et al , 2015).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%